2022
DOI: 10.1210/clinem/dgac312
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pituitary Hormone Genes in Subjects Who Died From COVID-19 Independently of Virus Detection in the Gland

Abstract: Context Involvement of the pituitary gland in SARS-CoV-2 infection has been clinically suggested by pituitary hormone deficiency in severe COVID-19 cases, by altered serum ACTH levels in hospitalized patients, and by cases of pituitary apoplexy. However, the direct viral infection of the gland has not been investigated. Objectives To evaluate whether the SARS-CoV-2 genome and antigens could be present in pituitary glands of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…TSH levels returned to baseline at follow-up suggesting that thyroid function alterations in patients with COVID-19 show rapid recovery [23]. These results about suppressed TSH levels in the acute phase of COVID-19 are supported by a recent study that showed suppressed mRNA of pituitary hormones and pituitary regulatory genes in lethal COVID-19 cases (n = 23) [46].…”
Section: Discussionsupporting
confidence: 58%
“…TSH levels returned to baseline at follow-up suggesting that thyroid function alterations in patients with COVID-19 show rapid recovery [23]. These results about suppressed TSH levels in the acute phase of COVID-19 are supported by a recent study that showed suppressed mRNA of pituitary hormones and pituitary regulatory genes in lethal COVID-19 cases (n = 23) [46].…”
Section: Discussionsupporting
confidence: 58%
“…The result agrees with White, Melissa C., et al 17 PCOS and infected with COVID-19, when compared with the healthy groups. These results are in agreement with Poma, A. et al 18 who found physiological and pathological conditions, of COVID-19, may affect the secretion of pituitary hormones. In a few cases, the infection was tracked down in cells of the adeno-and neurohypophysis 19 .…”
Section: Discussionsupporting
confidence: 93%
“…A recent autopsy study that detected the viral genome and antigens in both anterior and posterior hypophysis supports the pituitary tropism of SARS-CoV-2. Moreover, compared to controls, the transcription of TSH, FSH, and LH beta-subunits genes was strongly suppressed in pituitary infected by SARS-CoV-2 [ 13 ]. Abdillah et al showed that SARS-CoV-2 spike protein suppresses gonadotropin secretion from bovine pituitaries [ 14 ].…”
Section: Discussionmentioning
confidence: 99%